A STUDY ON THE IMPACT OF TOXOPLASMA GONDII ON THE COMMUNITY VIA GENETIC RESEARCH - Al-Safi, Mushtaq Talib (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Toxoplasma gondii is an obligate intracellular protozoan parasite with a global presence, infecting nearly all warm-blooded animals, including humans, and this research explores the genetic diversity, virulence, and host-pathogen interactions of T. gondii, emphasizing the prevalence and diversity of clonal lineages (Types I, II, III), atypical strains, and single nucleotide polymorphisms (SNPs), particularly in Hungary and Brazil. Method: Comprehensive genomic, proteomic, and transcriptomic methodologies were employed, utilizing advanced genetic tools such as multilocus microsatellite typing, CRISPR-Cas9 editing, and genome sequencing to identify virulence factors, host immune response pathways, and parasite adaptation mechanisms. Result: The study highlights how environmental and host genetic factors shape gene expression and pathogenic outcomes, with key insights from CRISPR-mediated gene disruptions, transcriptional profiling in infected macrophages, comparative genomics between T. gondii and related parasites, and case studies in Wisconsin and Brazil revealing geographic clustering and genotype-specific host outcomes, while efforts in vaccine development target rhoptry and microneme proteins. Novelty: Further, the research addresses ethical, regulatory, and public health dimensions, emphasizing biospecimen collection, community engagement, and global surveillance, contributing to a refined understanding of T. gondii’s biology and broader implications for public health, including standardized virulence evaluation protocols and integrated veterinary and epidemiological strategies.